The gut microbiota metabolite capsiate promotes Gpx4 expression by activating TRPV1 to inhibit intestinal ischemia reperfusion-induced ferroptosis. (1st January 2021) - Deng, Fan; Zhao, Bing-Cheng; Yang, Xiao; Lin, Ze-Bin; Sun, Qi-Shun; Wang, Yi-Fan; Yan, Zheng-Zheng; Liu, Wei-Feng; Li, Cai; Hu, Jing-Juan; Liu, Ke-Xuan
ABSTRACT: Ferroptosis, a new type of cell death has been found to aggravate intestinal ischemia/reperfusion (I/R) injury. However, little is known about the changes of gut microbiota and metabolites in intestinal I/R and the role of gut microbiota metabolites on ferroptosis-induced intestinal I/R injury. This study aimed to establish a mouse intestinal I/R model and ileum organoid hypoxia/reoxygenation (H/R) model to explore the changes of the gut microbiota and metabolites during intestinal I/R and protective ability of capsiate (CAT) against ferroptosis-dependent intestinal I/R injury. Intestinal I/R induced disturbance of gut microbiota and significant changes in metabolites. We found that CAT is a metabolite of the gut microbiota and that CAT levels in the preoperative stool of patients undergoing cardiopulmonary bypass were negatively correlated with intestinal I/R injury. Furthermore, CAT reduced ferroptosis-dependent intestinal I/R injury in vivo and in vitro. However, the protective effects of CAT against ferroptosis-dependent intestinal I/R injury were abolished by RSL3, an inhibitor of glutathione peroxidase 4 (Gpx4), which is a negative regulator of ferroptosis. We also found that the ability of CAT to promote Gpx4 expression and inhibit ferroptosis-dependent intestinal I/R injury was abrogated by JNJ-17203212, an antagonist of transient receptor potential cation channel subfamily V member 1 (TRPV1). This study suggests that the gut microbiota metabolite CAT enhances Gpx4 expression and inhibits ferroptosis by activating TRPV1 in intestinal I/R injury, providing a potential avenue for the management of intestinal I/R injury.